Land Procurement for the Public Interest - Fansiska Vivi Ganggas; Adonia Ivonne Laturette; La Ode Angga; Barzah Latupono (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2025)
The construction of various public facilities and other infrastructure requires land in large quantities and varying in size depending on the needs of a region. At the same time, as the population increases, there is less and less land available, and because the State does not have land for the construction of various public facilities and other infrastructure for the public interest mentioned above, efforts are needed to procure land for the construction of various public facilities and infrastructure. This research is a normative legal research, using a problem approach that includes the statutory approach (Statute Approach) and the conceptual approach (Conceptual Approach) as well as the case approach. With the statutory approach (statute approach) it is intended that as a legal research, the answer to the legal issue of this research uses related statutory regulations, and with these statutory regulations the relationship between one regulation and another can be analyzed as an inseparable series, especially statutory regulations related to the land acquisition process on customary lan. Public land acquisition for the benefit of objects with customary land ownership is customary land acquisition for the public interest that involves the recognition of customary rights through a deliberation process and appropriate compensation, based on the principles of humanity, justice, and welfare. The implementation of this land acquisition is regulated by Law Number 2 of 2012 and its implementing regulations, which mandate the involvement of customary law communities, customary leaders, and relevant agencies in the planning process through to the transfer of land rights.